Fetal gender ratio in recurrent miscarriages - Del Fabro A; Driul L; Anis O; Londero AP; Bertozzi S; Bortotto L; Marchesoni D (Dove Medical Press, 2011)
Anna Del Fabro1, Lorenza Driul1, Omar Anis1, Ambrogio P Londero1, Serena Bertozzi2, Livio Bortotto3, Diego Marchesoni11Clinic of Obstetrics and Gynecology, 2Clinic of Surgery, 3Unit of Genetics, University Hospital of Udine, Udine, ItalyBackground: The purpose of this study was to evaluate the gender ratio and incidence of chromosomal anomalies in the products of conception (POC) from recurrent miscarriages.Methods: We determined the karyotypes of POC from patients with recurrent spontaneous miscarriages between 1999 and 2009.Results: In total, 313 specimens were successfully karyotyped, with a median gestational age of 10 weeks at miscarriage (interquartile range 8–13); 199 (64%) were females and 114 (36%) were males. In total, 121 (39%) had abnormal karyotypes, the most prevalent of which were chromosome 21 and 16 trisomies, triploidy, and monosomy X.Conclusion: Our findings suggest that female POC might be more susceptible to recurrent miscarriages than male ones during embryogenesis, implantation, and initial fetal development.Keywords: fetal gender, recurrent miscarriages, karyotype anomalies